Advanced cancer : pain and quality of life - Chow, Edward; Merrick, Joav , 1950- (Health and human development, 2010)
An estimated 166,400 new cases of cancer occur in Canada in 2008. Bone metastases unfortunately remain a common site of recurrence, with breast and prostate cancer patients representing a substantial proportion of this population. Metastatic bone disease is associated with significant morbidity and mortality